2007
DOI: 10.3113/fai.2006.0804
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Screw-Augmented Intramedullary Fixation for Tibiotalocalcaneal Arthrodesis

Abstract: Use of an augmentation screw as described in this study may lead to lower complication rates, particularly in patients with osteopenic bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 21 publications
3
32
0
2
Order By: Relevance
“…Bu hastalarda stabiliteyi arttırmak için transvers yönelim yerine arkadan öne yönelimli distal kilitleme vidaları ya da kalkaneus-talus yönelimli ek transfiksasyon vidası kullanılması daha uygundur. [16,17] Biz de hastalarımızın üç tanesinde stabiliteyi artırmak amaçlı çivinin üzerinden kalkaneustan talusa yönelim-li kilitleme vidası kullandık.…”
Section: Discussionunclassified
“…Bu hastalarda stabiliteyi arttırmak için transvers yönelim yerine arkadan öne yönelimli distal kilitleme vidaları ya da kalkaneus-talus yönelimli ek transfiksasyon vidası kullanılması daha uygundur. [16,17] Biz de hastalarımızın üç tanesinde stabiliteyi artırmak amaçlı çivinin üzerinden kalkaneustan talusa yönelim-li kilitleme vidası kullandık.…”
Section: Discussionunclassified
“…3,9,10,13,14 The loads were designed to challenge, but not damage, the anatomic specimens, and this allowed sequential bending tests in different planes and torsional testing in both internal and external rotation directions on the same specimens.…”
Section: Discussionmentioning
confidence: 99%
“…This radiographic parameter allowed assessment especially of device fixation in the hindfoot, as well as a study of the failure pattern. Dorsiflexion was chosen since, according to O'Neill et al, 19,20 this represents the predominant loading mode of the arthrodesis site during weightbearing in the postoperative period. The size of the angle was adopted in light of preliminary tests which had shown that displacement by 7 degrees was clear and certain evidence of permanent, rather than of reversible elastic, deformation.…”
Section: Discussionmentioning
confidence: 99%